Narrow row spacing on soybean in the early and conventional sowing time in a subtropical region of Brazil - Foloni, José Salvador Simonetto; Abati, Julia; Henning, Fernando Augusto (Scientia Agraria Paranaensis, 2022)
Phytotechnical positioning procedures in soybean crop must be validated in the context of the interaction between genotype, environment and management. Thus, the aim of this work was to evaluate the agronomic performance of soybean cultivars sown in different row spacing, in early (October 8th) and conventional (November 12th) sowing dates in a subtropical climate region of southern Brazil. The experimental design was in an 18 × 2 factorial scheme, with four replications. The factors were constituted by 18 soybean cultivars (with a maturity group of 5.3 to 6.4) installed with row spacing of 25 and 50 cm. Final plant population, plant height, lodging, 1000-grains weight and grain yield were evaluated. The row spacing and the cultivar used interfere in the agronomic performance of soybean, regardless of sowing date. The narrow row spacing of 25 cm increases the 1000-grains weight and soybean grain yield, regardless of cultivar and sowing date in a subtropical climate region of southern Brazil, with the most pronounced augments in the conventional sowing date. In general, the most yield cultivars were M 5947 IPRO and M 6410 IPRO.